Er3+-Doped Upconversion Nanoparticle Coatings for Thermometric Microscanning: Tackling Experimental Factors - Aguilar, Alfredo M.; Saidman, Ezequiel L.; Rosato Siri, María Victoria; Marpegan, Luciano; Martínez, Eduardo David (American Chemical Society, 2023)
Fil: Aguilar, Alfredo M.. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina